(untitled) (Jurnal Huma Betang Demokrasi, 2021)
The policy for law enforcement for election crimes has been regulated in Law Number 7 of 2017 concerning General Elections, especially Articles 476 to 554. Although the policy for enforcing election acts has been regulated in such a way, the policy still needs to be studied more deeply about its implementation. The effectiveness and success of law enforcement on election crimes can be seen through three elements of the legal system, namely the legal structure, legal substance and legal culture. Based on the three elements of the legal system, it can be seen that there are issues regarding law enforcement for election crimes, which include: First, related to the legal substance in which policy materials in law enforcement of election crimes are still found to be problematic rules that cause debate or which have the potential to cause debate, regulations that are lacking clear, and a number of other issues; Second, related to the legal structure related to law enforcement institutions for election crimes held by the Gakkumdu Center which actually gave rise to an ineffective law enforcement bureaucracy; Third, related to the legal culture related to public participation, especially the issue of the lack of attention to legal protection for the community who acts as a reporter, witness or victim in handling election crimes. To unravel these problems, it is necessary to reform and reconstruct the law so that the law enforcement of election crimes can run effectively and be able to achieve the objectives of law enforcement, namely justice, benefit and certainty.